Regulation, innovation and disruption: the European Medicines Agency and adaptive licensing of pharmaceuticals. Issue 2 (2nd July 2020) - Syrett, Keith
ABSTRACT: Growing concerns over the related problems of speedily bringing innovative pharmaceuticals (especially so-called precision medicines) to market, and addressing areas of unmet medical need, have engendered critical scrutiny of the existing process for the licensing of pharmaceutical products. The objective is to enable these products to receive approval sooner, but on the basis of the provision of less complete evidence, than was previously the case. This article examines the attempts made to tackle this issue at European Union level, through a pilot programme exploring 'adaptive' approaches to licensing operated by the European Medicines Agency. Responses to this initiative indicate significant difficulty in securing regulatory legitimacy in this context. This suggests that innovative pharmaceutical technologies are disruptive of existing regulatory frameworks, such that future attempts to accommodate them within these may be susceptible to failure.